Representation Moral Message of Sacrifice by the Sandwich Generation in the Film Home Sweet Loan - Asriana Syamsudin; Ken Amasita Saadjad; Nurfita Waaso; Mohammad Dewantara; Sartika Hader (Jogjakarta Communication Conference (JCC), 2026)
The sandwich generation phenomenon refers to a situation where individuals in their productive years are forced to bear dual responsibilities: taking care of their parents and other family members who are still dependent on them. In Indonesia, the sacrifices made by those in the sandwich generation are often seen as a moral obligation of the family, without any consideration for the well-being of the individual. This perspective isn’t only reflected in social practices but is also perpetuated and legitimized through popular media, including films. This study aims to analyze the moral messages conveyed about the sacrifices of the sandwich generation in the film Home Sweet Loan, using Charles Sanders Peirce’s semiotic approach. A qualitative descriptive method was used in this research. The analysis focused on the relationships between signs, objects, and interpreters, thereby uncovering the moral messages conveyed in the film’s narrative. The results show that Home Sweet Loan portrays the sacrifices of the sandwich generation through the structural, emotional, and financial burdens faced by the main characters. Such sacrifices are presented as actions that are considered normal, often go unnoticed, and are imposed in the name of family responsibilities. Yet, the film also conveys important moral messages about the importance of empathy, equal roles within the family, the limits of sacrifice, and an individual’s courage in protecting their own well-being. This research contributes to the study of film semiotics and media studies by showing how films shape and challenge societal perceptions of the sandwich generation phenomenon in Indonesia.